2023
DOI: 10.1038/s41556-022-01071-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria regulate intracellular coenzyme Q transport and ferroptotic resistance via STARD7

Abstract: Coenzyme Q (or ubiquinone) is a redox-active lipid that serves as universal electron carrier in the mitochondrial respiratory chain and antioxidant in the plasma membrane limiting lipid peroxidation and ferroptosis. Mechanisms allowing cellular coenzyme Q distribution after synthesis within mitochondria are not understood. Here we identify the cytosolic lipid transfer protein STARD7 as a critical factor of intracellular coenzyme Q transport and suppressor of ferroptosis. Dual localization of STARD7 to the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 58 publications
4
37
0
Order By: Relevance
“…EFI2AK4/GCN2 or EFI2AK1/HRI , which sense mitochondrial dysfunction, were upregulated in the human tissues ( Fig S9B) . PGC-1α , which regulates mitochondrial biogenesis and quality control 88 , and GPX4 , AIFM2 , PARL , and STARD7 , which detoxify lipid-peroxidation and inhibit ferroptosis 89,90 , were strongly downregulated in the human heart and kidney. Their downregulation would elevate mROS and the innate immune response in these tissues ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EFI2AK4/GCN2 or EFI2AK1/HRI , which sense mitochondrial dysfunction, were upregulated in the human tissues ( Fig S9B) . PGC-1α , which regulates mitochondrial biogenesis and quality control 88 , and GPX4 , AIFM2 , PARL , and STARD7 , which detoxify lipid-peroxidation and inhibit ferroptosis 89,90 , were strongly downregulated in the human heart and kidney. Their downregulation would elevate mROS and the innate immune response in these tissues ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CoQ is a key antioxidant that protects cells from lipid peroxidation and ferroptosis, and is reduced to ubiquinol (CoQH 2 ) by FSP1 to exert its effect (Bersuker et al, 2019). Recent findings have confirmed that the StAR-related lipid transfer domain containing 7 (STARD7) is cleaved into two parts by presenilin-associated rhomboid-like (PARL) when entering the mitochondria (Deshwal et al, 2023). One part remained in the mitochondria to maintain the essential functions of this organelle, whereas the other part reduced the sensitivity of cancer cells to ferroptosis by transferring CoQ from the mitochondria to the cell membrane.…”
Section: Tumorigenesismentioning
confidence: 99%
“…3 Therefore, highly sensitive and precise imaging of specific mitochondrial miRNA in tumor cells that can inhibit ferroptosis could afford patent therapeutic opportunities for cancer treatment as well as innovative pathways for the development of anticancer drugs. 4 As a classical signal amplification strategy, hybrid chain reaction (HCR) has been widely used for highly sensitive miRNA analysis in living cells with various degrees of success. 5−8 Compared with the common enzyme-mediated isothermal amplification technique rolling ring amplification (RCA), which will affect the sensing performance and limit its wide biological application because the involvement of enzymes will cause the risk of inactivation in the complex cellular environment, HCR is a more ideal signal amplification method.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ferroptosis, as a new type of programmed cell death with significant clinical potentials, has attracted extensive attention in cancer treatment. , However, emerging evidence implicated that ferroptosis can be inhibited by specific mitochondrial miRNA in tumor cells, leading to the poor cancer treatment . Therefore, highly sensitive and precise imaging of specific mitochondrial miRNA in tumor cells that can inhibit ferroptosis could afford patent therapeutic opportunities for cancer treatment as well as innovative pathways for the development of anticancer drugs . As a classical signal amplification strategy, hybrid chain reaction (HCR) has been widely used for highly sensitive miRNA analysis in living cells with various degrees of success. Compared with the common enzyme-mediated isothermal amplification technique rolling ring amplification (RCA), which will affect the sensing performance and limit its wide biological application because the involvement of enzymes will cause the risk of inactivation in the complex cellular environment, HCR is a more ideal signal amplification method. , Despite progress made, an inevitable limitation is that traditional HCR can not be precisely controlled at the desired location and time because of the “always-active” state and the passive triggering patterns with initiator sequences .…”
Section: Introductionmentioning
confidence: 99%